Negative correlation between oil lipolysis and its LC-PUFA content in simulated digestion - Beltrame, Gabriele; Valta, Iida; Damerau, Annelie; Linderborg, Kaisa M. (Elsevier BV, 2026)
The growing awareness of the pro-oxidant conditions of the gastrointestinal tract promotes attention to the fate of n-3 PUFAs after ingestion. These investigations primarily rely on in vitro models, with INFOGEST 2.0 being the most commonly applied. However, scarce attention is currently paid to the hydrolysis degree of the oils. In the present short communication, lipid digesta of DHA-rich oils, obtained after in vitro digestion, were analyzed with NMR spectroscopy. Rapeseed oil was used as positive control. Results showed that the DHA content of the oil negatively affected lipolysis, with an observed negative non-linear relationship between lipolysis extent and the long chain n-3/n-6 fatty acid ratio of the oil. 13C NMR revealed a clear negative relationship between lipolysis and relative amount of 22:6n-3 in the sn-1,3 position. This intrinsic obstacle should be taken into account during the in vitro research on behavior of n-3-rich oils in the gastrointestinal tract.